ANALISIS SIKAP PENILAIAN PASIEN TENTANG JASA PELAYANAN KESEHATAN - Andri Purnamawati (JURNAL ILMU MANAJEMEN, 2014)
The study, entitled "Analysis of Patients About Attitude Assessment in Health Care Services Medical Center Health Care and Rehabilitation Center (PPKR) BSMI Prambanan Klaten" which aims to determine how attitudes outpatient assessment of health services provided by the Center for Health Services and Medical Center Rehabilitation (PPKR) BSMI Prambanan Klaten that includes, facilities, workforce and location.In this study, researchers used a test tool attidude towar object or model of Fishbein attitude to answer the hypothesis. The hypothesis that the attitude of the patient assessment of health care services that includes, facilities, workforce and location in the Medical Center Health Care and Rehabilitation Center (PPKR) BSMI Prambanan Klaten is positive, it is true and acceptable. Because after tested the hypothesis is proven, based on the patient's attitude about the assessment interval services Polyclinics Health Care and Rehabilitation Center (PPKR) BSMI Prambanan Klaten covering factors, facilities, workforce and location of 64.44 and enter the positive interval is 54.78 x 67.66, mean attitude positive patient assessment of services provided Polyclinics Health Care and Rehabilitation Center (PPKR) BSMI Prambanan Klaten.